Aplikasi Ekstrak Portulaca oleracea L. sebagai Biostimulan pada Pertumbuhan Kale (Brassica oleracea L. var acephala) - Millania Putri Shayen; Zozy Aneloi Noli; Suwirmen Suwirmen (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Biostimulants are organic compounds which in small amounts can have a positive effect on plant growth. Plant extracts are a source of biostimulants which contain compounds such as secondary metabolites and other organic compounds that can enhance plant growth. Portulaca is a wild plant that contains secondary metabolites, amino acids, macro and micro nutrients which have the potential as a source of biostimulants. Kale is a vegetable from the Brassicaceae family which is known as a super food because of its health benefits. Efforts to improve the quality of Kale production need to be increased in line with public demand. This study aims to analyze the effect of giving several concentrations of Portulaca extract and its compatibility on Kale growth. The method used in this study was an experimental method with a completely randomized design (CRD) with 5 treatments and 5 replications. Some concentrations of Portulaca extract are as a treatment consisting of: A (0%); B (1.5%); C (3%); D (4.5%); and E (6%). The application of Portulaca extract had a significantly different effect on chlorophyll and total chlorophyll of Kale plants with the highest content of 0.822 and 1.462, but did not have a different effect on other growth parameters. Based on proximate analysis, increasing the concentration of Portulaca extract can increase the highest percentage of protein content, namely at a concentration of 6% by 23.75%.